Giant Endometrial Polyp in a Postmenopausal Woman without Hormone/Drug Use and Vaginal Bleeding - Betül Ünal; Selen Doğan; Fatma Şeyda Karaveli; Tayup Şimşek; Gülgün Erdoğan; Işıl Candaner (Case Reports in Obstetrics and Gynecology)
The objective of this study is to determine and discuss the causes of a giant endometrial polyp in a postmenopausal woman without hormone/drug use and to submit interesting clinical presentation. Here we report a seventy-year-old female patient who was admitted to our hospital with lower back pain. There were no other complaints from her. Physical examination was normal. For further examination, computed tomography was performed and a heterogeneous mass, with a diameter of 10 × 9 centimeters, was detected in the uterine cavity. Hysterectomy because of suspected endometrial cancer was performed. Histopathological examination showed us a giant endometrial polyp with edematous and focal fibrotic stroma, large thick walled blood vessels between normal sized and cystically dilated endometrial glands. To the best of our knowledge, this is the first report of a giant endometrial polyp which is unrelated to use of drugs such as tamoxifen and raloxifene; however, based on the history of the patient it may be associated with long-term consumption of thyme, which is a kind of phytoestrogen.